2018
DOI: 10.1371/journal.pone.0198236
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of root-knot nematodes of the genus Meloidogyne Göeldi, 1892 (Nematoda: Meloidogynidae) associated with olive plants and environmental cues regarding their distribution in southern Spain

Abstract: Root-knot nematodes of the genus Meloidogyne are recognised worldwide as a major production constraint in crops of primary economic importance. Knowledge of their diversity and prevalence, as well as the major environmental and agronomical cues for understanding their distribution in specific areas is of vital importance for designing control measures to reduce significant damage. We provide the first detailed information on the diversity, distribution and levels of Meloidogyne species infecting wild and culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…The root-knot nematodes, Meloidogyne Göldi, 1892 (Rhabditida: Meloidogynidae) belongs to the most economically important plant that causes serious damage to most agricultural crops worldwide (Archidona-Yuste et al 2018 and Gareeb et al 2019). Meloidogyne incognita is the most common species of root-knot nematodes that infects almost all cultivated plants, which makes it perhaps the most damaging of pathogens (Khalil and Darwesh 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The root-knot nematodes, Meloidogyne Göldi, 1892 (Rhabditida: Meloidogynidae) belongs to the most economically important plant that causes serious damage to most agricultural crops worldwide (Archidona-Yuste et al 2018 and Gareeb et al 2019). Meloidogyne incognita is the most common species of root-knot nematodes that infects almost all cultivated plants, which makes it perhaps the most damaging of pathogens (Khalil and Darwesh 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Meloidogyne genus comprises more than 100 described species (Moens et al, 2009), 25 of which have been found in Europe (Wesemael et al, 2011;Archidona-Yuste et al, 2018;Santos et al, 2019). In Portugal, eight RKN species (M. arenaria, M. chitwoodi, M. hapla, M. hispanica, M. incognita, M. javanica, M. luci and M. lusitanica) have been found parasitizing several economically important crops (Pais & Abrantes, 1989;Abrantes & Santos 1991;Abrantes et al, 2008;Conceic ßão et al, 2009;Esteves et al, 2015;Maleita et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The olive tree rhizosphere has been found to be a good habitat for many species of plant-parasitic nematodes (Castillo et al 2010;Ali et al 2014). Only some of them, however, have been shown to be pathogenic or to directly feed on olive roots, among which one of the most widespread and damaging is the genus Meloidogyne (Castillo et al 2010;Ali et al 2014;Archidona-Yuste et al 2018). A number of species of this genus have been found to infect olive (Tarjan 1957;Minz 1961;Yang and Zhong 1980;Abrantes et al 1991;Castillo et al 2003;Archidona-Yuste et al 2018): M. javanica (Treub, 1885) Chitwood, 1949M.…”
Section: Introductionmentioning
confidence: 99%
“…Only some of them, however, have been shown to be pathogenic or to directly feed on olive roots, among which one of the most widespread and damaging is the genus Meloidogyne (Castillo et al 2010;Ali et al 2014;Archidona-Yuste et al 2018). A number of species of this genus have been found to infect olive (Tarjan 1957;Minz 1961;Yang and Zhong 1980;Abrantes et al 1991;Castillo et al 2003;Archidona-Yuste et al 2018): M. javanica (Treub, 1885) Chitwood, 1949M. incognita (Kofoid & White, 1919) Chitwood, 1949, M. hapla Chitwood, 1949, M. arenaria (Neal, 1889) Chitwood, 1949, M. lusitanica Abrantes & Santos, 1991, M. baetica Castillo, Vovlas, Subbotin & Troccoli, 2003, and M. oleae Archidona-Yuste, Cantalapiedra-Navarrete, Liebanas, Rapoport, Castillo & Palomares-Rius, 2018 The aforementioned Meloidogyne spp.…”
Section: Introductionmentioning
confidence: 99%